RADIOMETRIC CALIBRATION PERFORMANCE OF A MULTISPECTRAL CAMERA WITH A SINGLE SENSOR AND MULTIPLE HEADS - Porto, L. R. [UNESP]; Imai, N. N. [UNESP]; Tommaselli, A. M.G. [UNESP]; Salvador Neto, L. (Copernicus Publications, 2022)
Radiometric calibration of remote sensing images can be performed with many existing techniques. The selected method depends on the sensor type, application and user's prior knowledge. The main objective of this study was to analyse the radiometric calibration technique proposed by Agrowing to process the data acquired for a multispectral camera with a single sensor and multiple heads. This radiometric calibration can be done in a simple way by a regular user and just needs an image from the X- rite Classic 24, a small panel with 24 colours, under the same viewing angle as the data acquisition. The dual-head camera was used to acquire images in two illumination conditions. The non-calibrated and calibrated DN pixels values were evaluated by comparing the reflectance factor calculated from radiance measurement, acquired by a ASD spectrometer followed by a linear adjustment. The results show that in the visible bands the non-calibrated and calibrated DN have a strong correlation with ASD reflectance factor. The NIR band presents the weakest correlation, but with a slight improvement after the radiometric calibration. The red-edge band presented a larger improvement with the application of the calibration procedure.
Keywords: Agriculture; Camera Calibration; Image Processing; Multiple Heads Sensor; Multispectral Image